A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas - Enghoff, Henrik (Zootaxa, 2017)
The new genus Tropostreptus is erected to accommodate seven species which are all endemic in Tanzania: T. hamatus (Demange, 1977) (type species, = Spirostreptus hamatus Demange, 1977), T. sigmatospinus sp. nov., T. microcephalus sp. nov., T. droides sp. nov., T. kipunji spec. nov., T. austerus (Attems, 1950) (= Epistreptus austerus Attems, 1950) and T. severus sp. nov. All but one (T. sigmatospinus) of the species are restricted to the Eastern Arc Mts. in a wide sense, i.e., including Mt. Rungwe. Notes are included on Rickia gigas Santamaria et al., 2016 (Ascomycota: Laboulbeniales), which infects several Tropostreptus species. The typical, long-celled form of R. gigas grows on body parts of both sexes coming into contact during copulation, whereas a short-celled form also ascribed to R. gigas grows on the hind margin of body rings of both sexes. A key to Tropostreptus species is included.